Pemanfaatan Augmented Reality Sebagai Media Interaktif Dalam Pameran Seni Lukisan - Sutrisna, Sutrisna; Aulia, Rachmat; Sundari, Siti (Journal Global Technology Computer, 2024)
Art exhibitions as a means of displaying creative works require innovation in the interaction between visitors to artworks. Currently, the use of augmented reality (AR) in art exhibitions is increasingly relevant and attracts attention as an interactive medium. However, challenges in its implementation still exist, including the lack of visitor engagement and limited physical space. The proposed solution is to use the marker-based tracking method in AR, which allows the integration of artworks with the environment through visual markers. This method allows visitors to interact directly with artworks through their mobile devices. In this context, the marker-based tracking method uses physical and visual markers, such as images or certain objects, to trigger AR elements. Visitors can access additional content, such as information about the artwork, multimedia interactions, or dynamic visualizations, by pointing their devices at the specified markers. This creates a new dimension in art, allowing visitors to interact directly with artworks through additional digital layers. The result is increased visitor interaction and participation in art exhibitions, resulting in a more immersive and dynamic experience. This system is expected to broaden the appreciation of art, encourage discussion, and enrich the visitor experience. The main goal is to enrich the visitor experience in understanding, appreciating, and enjoying artworks through interactive and innovative technology. Thus, the use of AR in art exhibitions with the marker-based tracking method not only creates a creative and immersive experience, but also opens up new potential in connecting art and technology to create a richer and more memorable experience. The results achieved from this study are in the form of providing a deeper experience to visitors in a painting art exhibition.